High prevalence of anti-Strongyloides antibody in SARS-CoV-2-infected human sera in a Thai hospital: Rapid serological screening - Lakkhana Sadaow; Patcharaporn Boonroumkaew; Rutchanee Rodpai; Oranuch Sanpool; Prinya Prasongdee; Pewpan M. Intapan; Wanchai Maleewong (Elsevier, 2024)
COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can stimulate a systemic inflammatory response with severe lung involvement, multisystem dysfunction, and death in some cases. Immunosuppressive treatments have been proposed for management of COVID-19 patients, but these bring the risk of flare-up of pre-existing infections. Strongyloidiasis can become severe or fatal in immunocompromised individuals. This cross-sectional study determined the prevalence of anti-Strongyloides IgG antibody in sera collected from SARS-CoV-2 infected persons in a tertiary-care Thai hospital from January 2021 to January 2022. The survey was conducted using a rapid immunochromatographic test (ICT) kit based on a recombinant antigen of Strongyloides stercoralis known to be IgG-immunoreactive. High prevalence of anti-Strongyloides IgG antibody was found. Out of 297 SARS-CoV-2-infected patients 117 (39.4 %, 95 % CI 33.8-45.2 %) were positive for S. stercoralis according to the ICT kit. In areas where strongyloidiasis is endemic, we suggest using this point-of-care ICT kit for routine rapid screening in seriously ill COVID-19 patients who will be subjected to immunosuppressive treatment. Prompt anthelminthic treatment should be administered to prevent serious systemic strongyloidiasis in at-risk patients.